Proposed interior design scheme of Zellon Sri Andaman one stop centre at Lot 98503, No 140 Jalan Ma’arof, Taman Bandaraya, 59100 Kuala Lumpur / Siti Nadhirah Knan Nasir - Knan Nasir, Siti Nadhirah (Faculty of Architecture, Planning and Surveying, 2012)
The final project of Interior Design is the manifestation for student to understanding and organize a final year project.AII basic and presentation level design proposal that has been studies must be connected to the project that has been decided.There are a lot of One Stop Centerboutique near all over malaysia.To succeed in this business,the client have to rethink their existing work,business stategic and target market to see if more competitive advantage can be secured. This proposal is to open new one stop center of zellon sri andaman at lot 98503,no 140 jalan ma’arof ,taman bandaraya , 59100 kuala lumpur.The aim of this project is to fulfill the customer needs and save their time from been wasting to follow their wedding list require. The main objective is to follow the characteristic that has been told by the client, is ‘Malay’, ‘Exclusive’ , ‘Muslimah’ and ‘Terengganu’ .The design schematic that been prepared done so,it can be continues by study about their space planning that suitable with all four main point.so.the planning has been produce must be linked to concept,the images and charactheristic.From the research and observation conducted with all data and detail gathered was used as a guideline for the development ideas.